2019
DOI: 10.1101/694877
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Gsα stimulation of mammalian adenylate cyclases regulated by their hexahelical membrane anchors

Abstract: Mammalian adenylate cyclases (ACs) are pseudoheterodimers with dissimilar hexahelical membrane-anchors, isoform-specifically conserved for more than half a billion years. We exchanged both membrane anchors of the AC isoform 2 by the isosteric quorum-sensing receptor from Vibrio, CqsS, which has a ligand, Cholera-Autoinducer-1 (CAI-1). In the chimera, AC activity was stimulated by Gsα, CAI-1 had no effect. Surprisingly, CAI-1 inhibited Gsα stimulation. We report that Gsα stimulation of human AC isoforms 2, 3, 5… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(17 citation statements)
references
References 35 publications
1
16
0
Order By: Relevance
“…It is clear that the HD region plays a vital part in AC and GC assembly and stability. This is evident from our experiments with the M. intracellulare Cya ( 17 ), as well as the results of others using Cya and mammalian ACs as model enzymes ( 10, 26, 28 ). It remains to be determined whether any agents can elicit conformational changes in the membrane domain of Cya (or in any of the mammalian membrane ACs), leading to substantial changes in the HD similar in scale to the changes observed in the sGC during its activation.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…It is clear that the HD region plays a vital part in AC and GC assembly and stability. This is evident from our experiments with the M. intracellulare Cya ( 17 ), as well as the results of others using Cya and mammalian ACs as model enzymes ( 10, 26, 28 ). It remains to be determined whether any agents can elicit conformational changes in the membrane domain of Cya (or in any of the mammalian membrane ACs), leading to substantial changes in the HD similar in scale to the changes observed in the sGC during its activation.…”
Section: Discussionsupporting
confidence: 87%
“…The two functions are not mutually exclusive, as the ligand interactions with the membrane region of the AC may influence the HD assembly and thus regulate the cyclase function. Previous work utilizing chimeric constructs composed of fragments of the quorum sensing receptor CqsS from Vibrio harveyi and Cya ( 20 ) or mammalian membrane ACs ( 28 ) revealed that the membrane anchors of the ACs may act as orphan receptors for yet unknown ligands. Together with the proposed functional coupling between the TM domain and the catalytic site of Cya, the structure described here is consistent with these findings, offering molecular insights into the potential receptor role of the membrane anchor of a model membrane AC.…”
Section: Discussionmentioning
confidence: 99%
“…because we expected to characterize an inhibitory input (Graziano, Freissmuth et al, 1991, Seth et al, 2020. Most surprisingly, we discovered that 1-stearoyl-2-docosahexaenoyl-phosphatidic acid (SDPA) potentiated mAC3 up to 7-fold above the 16-fold activation already exerted by 600 nM Gsα alone (Fig.…”
Section: Lipids As Possible Mac Effectorsmentioning
confidence: 90%
“…We then carried out a lipidomic analysis with the pH 1 and the pH 6 fractions (Matyash, Liebisch et al, 2008, Vvedenskaya, Rose et al, 2021. Based on our previous data we expected ligands which inhibit Gsα-activated mAC activities (Seth et al, 2020). Therefore we concentrated on lipids prevalent in the pH 1 fraction.…”
Section: Lipids As Possible Mac Effectorsmentioning
confidence: 99%
See 1 more Smart Citation